PEMBELAJARAN MUSIK ANSAMBEL SISWA KELAS VIII 1 DI SMP NEGERI 3 KOTO BARU DHARMASRAYA - Sonya Cintya; Syeilendra Syeilendra (SENDRATASIK UNP, 2018)
Abstract This article is aimed to describe simple ensemble music learning and as an illustration/reference for teachers in teaching students about playing simple music ensembles of 8th grade Junior High School students at SMP Negeri 3 Koto BaruDharmasraya. This study used a descriptive approach. The instrument of this research was the researcher and assisted with supporting instruments such as stationery, audiovisuals and Smartphone. Techniques of data collection were done by library research, field observations, interviews and documentation. Techniques of data analysis were done by describing, elaborating and concluding. The results showed that the implementation of ensemble music learning by the teacher have not been fully using Lesson plan as a reference in learning. The methods that should be used by the teacher are question and answer method and demonstration. In fact, the teacher is more likely to use the lecturing method while the two methods written in the lesson plan have not been implemented into the learning process. The inequality of students` ability playing music leads the output obtained by students becomes varied. Lack of guided training given by teachers to students makes the ability to play musical instruments by the students is still not optimal. Keywords: Learning, ensemble music